FRI0067 Changes in Multi-Biomarker Disease Activity (MBDA) Score Correlate with Changes in Established Disease Activity Measurements in Patients with Early Ra from The Opera Study. (15th July 2016) - Brahe, C.H.; Østergaard, M.; Johansen, J.; Defranoux, N.; Hwang, C.-C.; Bolce, R.; Sasso, E.; Hørslev-Petersen, K.; Steengaard-Pedersen, K.; Junker, P.; Ellingsen, T.; Ahlquist, P.; et al.
Abstract : Background: No single biomarker has yet been able to predict disease course in patients with rheumatoid arthritis (RA). However combinations of biomarkers and changes therein early during treatment may be predictive of later treatment response. Objectives: Investigate correlations between early changes (Δ) in the validated multi-biomarker disease activity (MBDA) score and Δ in disease activity measurements – Disease Activity Score (DAS28-CRP), Clinical Disease Activity Index (CDAI), Simplified Disease Activity Index (SDAI) and C-reactive protein (CRP) – in early RA patients (the OPERA cohort). Methods: In the randomized double-blinded OPERA trial, 180 treatment-naive patients were randomized to an adalimumab (ADA) group (oral methotrexate (MTX) in combination with ADA) or a placebo group (oral MTX and placebo-ADA). Intra-articular glucocorticoids were also injected into swollen joints (1). DAS28-CRP, CDAI, SDAI, and CRP were measured at baseline (BL) and at 3, 6 and 12 months. MBDA score, calculated based on serum concentrations of CRP, interleukin-6, chitinase-3-like protein 1, vascular endothelial growth factor A, matrix metalloproteinase 1 and 3, vascular cell adhesion molecule 1, epidermal growth factor, tumor necrosis factor receptor type I, serum amyloid A, leptin and resistin, with a range of 1–100, was determined retrospectively at the same time points on banked serum samples (2). Correlations between ΔMBDA scores and Δ disease activity measurements were analyzed by Spearman's correlation coefficient. Results: Patients had a median age of 55.2 (range: 18.7–86) years, disease duration of 84 (range: 42–214) days; 66% were female; 72% and 65% were RF and anti-CCP positive, respectively. At BL, median DAS28-CRP was 5.6 (3.3–8.6) and median MBDA score was 59 (12–90). MBDA scores were low (<30) in 8 (4%) patients, moderate (30–44) in 25 (14%) and high (>44) in 147 (82%) patients. There were no statistically significant correlations between BL MBDA score and other disease activity measurements at 3 or 6 months in the placebo or ADA groups. Median ΔMBDA scores from BL to 3 months (ΔMBDA score0–3m ) and to 6 months (ΔMBDA score0–6m ) were -16.5 and -20, respectively. Median ΔDAS28-CRP from BL to 6 months (ΔDAS28-CRP0–6m ) and to 12 months (ΔDAS28-CRP0–12m ) were -2.9 and -3.2, respectively. ΔMBDA score0–3m and ΔDAS28-CRP0–6m were significantly correlated in the placebo and ADA groups, as were ΔMBDA score0–6m and ΔDAS28-CRP0–12m . ΔMBDA score0–3m also significantly correlated with ΔDAS28-CRP, ΔCDAI, ΔSDAI and ΔCRP from BL to 6 months and from BL to 12 months (Table 1 ). Conclusions: In patients with early RA from the OPERA cohort, ΔMBDA score from BL to 3 or 6 months were correlated with longer-term ΔDAS28-CRP, ΔCDAI, ΔSDAI and ΔCRP. Correlations were generally similar between treatment groups. References: Hørslev-Petersen K, et al., Ann Rheum Dis 2014; 73:654–661 Hirata et al. Current Biomarker Findings 2015, 5:69–78 Disclosure of Interest: C. H. Brahe: None declared, M. Østergaard Grant/research support from: Abbvie, BMS, Boehringer-Ingelheim, Eli Lilly, Janssen, Merck, Pfizer, Roche, UCB, Celgene, Sanofi, Regeneron, Novartis, T.Jensen, J. Johansen: None declared, N. Defranoux: None declared, C.-C. Hwang: None declared, R. Bolce: None declared, E. Sasso: None declared, K. Hørslev-Petersen: None declared, K. Steengaard-Pedersen Grant/research support from: Meda, Abbvie, Roche, Speakers bureau: UCB, Pfizer, P. Junker: None declared, T. Ellingsen: None declared, P. Ahlquist: None declared, H. Lindegaard Grant/research support from: Boehringer Ingelheim, A. Linauskas: None declared, A. Schlemmer Grant/research support from: Abbvie, Roche, MSD, M. Dam: None declared, I. Hansen: None declared, T. Lottenburger: None declared, C. Ammitzbøll: None declared, A. Jørgensen: None declared, S. Krintel: None declared, J. Raun: None declared, M. Hetland: None declared